Vietnam : Export Performance in 1999 and Beyond - World Bank (Washington, DC, 2013)
Changes in trade policies have been an essential component of the "doi moi" policy implemented by the Government of Vietnam since 1986. Over the years, most export quotas have been lifted and export taxes have been reduced to generally low levels. In addition, export activities by the private sector (both domestic and foreign) have been increasingly encouraged, thus breaking the trade monopoly of a small number of state-owned enterprises. These reforms -together with sound macroeconomic management- have led to a rapid export and import growth. The structure of exports also changed. During the 1990s, Vietnam started to exploit its comparative advantage in labor-intensive manufactures. Export growth was led by light manufactures, dominated by the garment and footwear sectors. Also remarkable, despite the shrinking share of agricultural goods in total exports, was the strong rise in the volume of rice exports. In only few years Vietnam turned from being a net rice importer into the world's second largest exporter. The Asian crisis has interrupted Vietnam's trade expansion. In 1998, exports increased by a sluggish 2.1 percent. To avoid an external deficit, the Government imposed additional import restrictions which, together with slumping domestic demand, led to a 0.8% decrease in the value of imports. Of course, this downturn in export performance was not unique to Vietnam. It was observed across Asia. What is surprising, however, is the exceptional magnitude of the recovery in 1999. Table 3 shows that in 1999, Vietnam's exports grew by an impressive 23.4 percent, much faster than in most other Asian countries. While Indonesia is still struggling to recover from the crisis, exports expanded at a quick pace in Korea, Malaysia and the Philippines. None of these countries, however, came close to Vietnam's astonishing rate of export growth. As can be seen in this report, Vietnam's recovery is not exclusively an oil-related phenomenon. Non-oil exports also grew at a fast 16.3 percent. This paper takes a detailed look at the factors that explain this strong export performance in 1999 and asks whether such a high rate of export growth can be sustained in the year 2000 and beyond. The analysis relies on two type of sources: official trade data collected by the General Statistical Office (GSO) and Vietnam Customs, as well as information collected during a visit of 16 companies in the footwear and garment industries in Hanoi, Hai Phong, Bien Hoa and Ho Chi Minh City in May-June 2000. The visit included seven private domestic companies, four private foreign-owned enterprises, and five public enterprises. All these companies were among the largest and fastest growing exporters in 1999.